1997
DOI: 10.1055/s-2008-1035131
|View full text |Cite
|
Sign up to set email alerts
|

Diodenlaser-Zyklophotokoagulation in der Behandlung therapierefraktärer Glaukome

Abstract: This study suggests that contact diode laser cyclophotocoagulation is an effective method and a valid alternative to cyclocryocoagulation in the treatment of refractory glaucoma including congenital glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 4 publications
(6 reference statements)
2
7
0
3
Order By: Relevance
“…The success rate in this study was 36.7% after 24 months. These results are comparable with the data of other authors in primary open-angle glaucoma and pseudoexfoliative glaucoma [2,3,8,9,12,[15][16][17][18][20][21][22]. For primary open-angle glaucoma success rates range from 75 to 90% after 1 year [12,13,16,21].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The success rate in this study was 36.7% after 24 months. These results are comparable with the data of other authors in primary open-angle glaucoma and pseudoexfoliative glaucoma [2,3,8,9,12,[15][16][17][18][20][21][22]. For primary open-angle glaucoma success rates range from 75 to 90% after 1 year [12,13,16,21].…”
Section: Discussionsupporting
confidence: 90%
“…This is due to a lower preoperative IOP (median: 21 mmHg; 5-95% quantile: 12-36 mmHg) compared with 32 mmHg up to 42 mmHg in other reports [2,3,8,9,12,[15][16][17][18][20][21][22]. Studies with comparable preoperative IOP values showed comparable IOP reductions [13,19].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…According to the guidelines published by the European Glaucoma Society (EGS), however, CPC should be used only if a filtering procedure is likely to fail or has already failed [5]. Transscleral diode laser cyclophotocoagulation has been used successfully in the treatment of refractory glaucoma, with an overall success rate of between 35 and 85 % [6][7][8][9][10][11][12][13][14][15][16][17]. Although CCT is no longer recommended by the EGS [5], the data pool available to date on the use of both CPC [18][19][20][21][22] and CCT [23,24] as primary therapy in patients with open-angle glaucoma cannot be regarded as extensive.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the procedure is reserved for patients with advanced (often secondary) glaucoma, which is refractory to medical or other surgical treatment [10]. In heterogeneous glaucoma populations overall success rates between 35% and 85% were reported [1,2,11,16,21,22,25,27]. The incidence of side effects seems to be significantly lower with contact diode laser cyclophotocoagulation than with other cyclodestructive procedures (cyclocryocoagulation, non-contact Nd:YAG laser cyclophotocoagulation).…”
Section: Introductionmentioning
confidence: 99%